Myasthaenia Gravis - a clinical case-report - Vaz Marques, Paula (2001)
Myastheania gravis is an autoimmune diseaseaffecting the neuromuscular junction, in whichautoantibodies are synthesized against thepostsynaptic nicotinic acetylcholine receptors. Thisautoimmune attack results in predominantly bulbarmuscle weakness and fatigability on repetitive use.The authors present a clinical case and discussthe aetiopathogenesis, clinical manifestations,diagnosis and treatment of myastheania gravis.